Postawa św. Atanazego i św. Hilarego wobec decyzji synodu w Ancyrze (358) - Grzywaczewski, Józef (Vox Patrum, 2015)
The Synod of Ancyra was organized at 358 by Basil, bishop of this city. The bishops who took part in this Synod published a Synodical Letter, called in English Manifesto. They presented in this letter the essence of the Homoiousian theology (it also written Homoeousians). They did not accept the Nicaean concept of equality of the Son to the Father, expressed by the term homoousios (consubstantial). They proposed other idioms, especially homoios kat ousian (similar to the Father according the essence); sometimes they used the term homoiousios (similar to the Father in all things). According to the teaching of the Homoiousians, the Son possessed the Divinity not in himself, but by the participation in Father’s Divinity. Athanasius of Alexandria expressed quite positive opinion about the theology of the Synod of Ancyra. Maybe he did know it very well; maybe he tried to see positive elements in it, because the Homoiousians were in opposition to the extreme Arianism. Hilary of Poitiers expressed also a positive opinion about the Manifesto of Ancyra. He appreciated its moderate position in Christology in comparison to the extreme Arians. He supposed that the above mentioned terms used by the bishops of Ancyra had the same meaning as the Nicaean term homoousios. Both Athanasius and Hilary did not pay much attention on terms but especially on the relation of the Son to the Father; he distinguished the identity of each Person; he was conscious of the difference of their mission, and he underlined the equality of their Divine nature and dignity.